2020
DOI: 10.1002/adhm.202000186
|View full text |Cite
|
Sign up to set email alerts
|

Durable Antibacterial Cotton Fabrics Based on Natural Borneol‐Derived Anti‐MRSA Agents

Abstract: In article number 202000186 by Liangzhi Hong, Jianyu Su and coworkers, a water‐soluble antibacterial agent is developed by integrating membrane‐active natural borneol with a hydrophilic PDMAEMA chain. Cotton fabrics with sustained antibacterial activity can be fabricated by grafting the borneol‐based antibacterial agents on the surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 57 publications
0
42
0
Order By: Relevance
“…In order to effectively control the microorganisms and reduce possible bacterial infections, the introduction of antibacterial materials is an effective strategy to eliminate bacteria and avoid serious infections [4]. In recent years, a variety of antibacterial agents such as chitosan [5], metal oxides [6], quaternary ammonium salts [7], peptides [8], and guanidine polymers [9] have been used in antibacterial finishing for cotton fabrics.…”
Section: Introductionmentioning
confidence: 99%
“…In order to effectively control the microorganisms and reduce possible bacterial infections, the introduction of antibacterial materials is an effective strategy to eliminate bacteria and avoid serious infections [4]. In recent years, a variety of antibacterial agents such as chitosan [5], metal oxides [6], quaternary ammonium salts [7], peptides [8], and guanidine polymers [9] have been used in antibacterial finishing for cotton fabrics.…”
Section: Introductionmentioning
confidence: 99%
“…The oxygenated monoterpene cavacrol is a well-known and efficient antimicrobial agent that can damage the cell membrane or other cytoplasmic targets passing through the altered phospholipid bilayer [ 14 , 15 , 16 ]. Similarly, the bicyclic monoterpene borneol is also a powerful and broad-spectrum antimicrobial agent able to alter the membrane structural and functional integrity [ 17 ]. In addition, other volatile compounds present in lower percentages can also contribute to the biological activity of the EO, including γ -terpinene, linalool and thymol [ 18 , 19 , 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…The 1,8-cineole, as the most predominant component of R. beesianus EO, has been demonstrated to have significant antibacterial activity [ 19 , 20 ]. Recent studies have shown that borneol has an effective broad-spectrum antibacterial capability against Gram-positive, Gram-negative bacteria, and even multi-drug resistant bacteria via membrane disruption mechanism [ 21 ]. According to the study of Donadu et al, EO rich in 1,8-cineole and α-pinene showed significant antibacterial against Staphylococcus aureus and methicillin-resistant Staphylococcus aureus with minimum inhibitory concentrations (MIC) and minimum lethal concentration (MLC) values from 2 to 4% ( v / v ) [ 22 ].…”
Section: Resultsmentioning
confidence: 99%